ANALYSIS OF INDEPENDENT CLAUSES IN THE TEXT OF PRESIDENT PRABOWO SUBIANTO'S INAUGURATIVE SPEECH - Riyadi, Rofiq; Nadyatunnisa, Gina; Tsabitha A N, Alya; Lisnawati, Iis (Media Inovasi Pendidikan dan Publikasi, 2025)
This study aims to analyze the use of independent clauses in President Prabowo Subianto’s inaugural speech from the perspective of Indonesian syntax. An independent clause is a grammatical unit consisting of a subject and predicate that can stand alone as a complete sentence. This research applies a qualitative approach with descriptive analysis techniques on the official speech transcript. The analysis identified eight independent clauses categorized into transitive verbal clauses, intransitive verbal clauses, and nonverbal clauses. Each clause was examined based on its structure and contextual use within the speech. The findings highlight the crucial role of independent clauses in enhancing message clarity and strengthening rhetorical leadership style. This study is expected to enrich syntactic studies and serve as a reference for Indonesian language education, particularly in understanding clause structures in formal contexts.